Relationship between Tibia Length Measurements and Standing Height: A Prospective Regional Study among Adolescents in Southern Region of Kosovo - Jovan Gardasevic; Bojan Masanovic; Fitim Arif (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The purpose of this research is to examine standing height in both Kosovan genders in the Southern Region as well as its association with tibia length, as an alternative to estimating standing height. A total of 225 individuals (120 male and 105 female) participated in this research. The anthropometric measurements were taken according to the protocol of ISAK. The relationships between body height and tibia length were determined using simple correlation coeffi cients at a ninety-fi ve percent confi dence interval. A comparison of means of standing height and tibia length between genders was performed using a t-test. After that a linear regression analysis were carried out to examine extent to which tibia length can reliably predict standing height. Results displayed that Southern Kosovan male are 178.60±5.73 cm tall and have a tibia length of 39.93±2.34 cm, while Southern Kosovan female are 165.33±4.45 cm tall and have a tibia length of 35.50±2.07 cm. The results have shown that both genders made Southern-Kosovans a tall group, but shorter than general Kosovan population. Moreover, the tibia length reliably predicts standing height in both genders; but, not reliably enough as arm span. This study also confi rms the necessity for developing separate height models for each region in Kosovo as the results from Southern-Kosovans don't correspond to the general values.